Innovative teaching of anthropometric through morphosis-dual function chair design and build - Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Abdullah, Fadzidah; Yusof, Zeenat Begam (Centre of Engineering and Built Environment Education Research (PeKA) Faculty of Engineering and Built Environment Universiti Kebangsaan Malaysia, 2019)
This research is about innovative teaching methodology and the learning process of anthropometric study using “Morphosis Dual-Function Chair Design and Build”. The objectives of the study are to develop their knowledge in anthropometrics and ergonomic study and to familiarise first-year architecture students about the functional requirement and creative aspects of design. The teaching methodology starts with a brief formulation, brief overview, design critique sessions, product making, and presentation. A survey on students’ feedback on their learning outcomes was conducted and the findings were analyzed to establish students’ understanding of the project’s objectives. In conclusion, both objectives have been achieved. Furthermore, students have also learned about teamwork and construction methods.